Microhardness of Ni-Cr alloys under different casting conditions Microdureza de ligas de Ni-Cr fundidas sob diferentes condições - José Roberto de Oliveira Bauer; Alessandro Dourado Loguercio; Alessandra Reis; Leonardo Eloy Rodrigues Filho (Sociedade Brasileira de Pesquisa Odontológica, 2006)
This study evaluated the microhardness of Ni-Cr alloys used in fixed prosthodontics after casting under different conditions. The casting conditions were: (1-flame/air torch) flame made of a gas/oxygen mixture and centrifugal casting machine in a non-controlled casting environment; (2-induction/argon) electromagnetic induction in an environment controlled with argon; (3-induction/vacuum) electromagnetic induction in a vacuum environment; (4-induction/air) electromagnetic induction in a non-controlled casting environment. The 3 alloys used were Ni-Cr-Mo-Ti, Ni-Cr-Mo-Be, and Ni-Cr-Mo-Nb. Four castings with 5 cylindrical, 15 mm-long specimens (diameter: 1.6 mm) in each casting ring were prepared. After casting, the specimens were embedded in resin and polished for Vickers microhardness (VH) measurements in a Shimadzu HMV-2 (1,000 g for 10 s). A total of 5 indentations were done for each ring, one in each specimen. The data was subjected to two-way ANOVA and Tukey's multiple comparison tests (alpha = 0.05). The VH values of Ni-Cr-Mo-Ti (422 ± 7.8) were statistically higher (p < 0.05) than those of Ni-Cr-Mo-Nb (415 ± 7.6). The lowest VH values were found for Ni-Cr-Mo-Be (359 ± 10.7). The VH values obtained in the conditions induction/argon and induction/vacuum were similar (p > 0.05) and lower than the values obtained in the conditions induction/air and flame/air torch (p < 0.05). The VH values in the conditions induction/air and flame/air were similar (p > 0.05). The microhardness of the alloys is influenced by their composition and casting method. The hardness of the Ni-Cr alloys was higher when they were cast with the induction/air and flame/air torch methods. Este estudo avaliou a microdureza de ligas de Ni-Cr usadas em prótese fixa fundidas sob diferentes condições. As condições de fundição foram: (1-maçarico) chama composta por uma mistura de gás/oxigênio e centrífuga sem o controle do ambiente de fundição; (2-indução/argônio) indução eletromagnética com o ambiente controlado com argônio; (3-indução/vácuo) indução eletromagnética com o ambiente sob vácuo; (4-indução/ar) indução eletromagnética sem o controle da atmosfera. Foram utilizadas três ligas: Ni-Cr-Mo-Ti, Ni-Cr-Mo-Be e Ni-Cr-Mo-Nb. Foram realizadas 4 fundições com 5 espécimes cilíndricos de 15 mm de comprimento (diâmetro de 1,6 mm). Depois das fundições os espécimes foram embutidos e polidos para as mensurações de microdureza Vickers (VH) em um Shimadzu HMV-2 (1.000 g por 10 s). Um total de 5 indentações foram feitas por anel, uma em cada espécime. Os dados de VH foram avaliados pelos testes de ANOVA e Tukey (alfa = 0,05) para contraste de média. A microdureza das ligas apresentou a seguinte ordem: Ni-Cr-Mo-Ti (422 ± 7,8) > Ni-Cr-Mo-Nb (415 ± 7,6) > Ni-Cr-Mo-Be (359 ± 10,7), sendo diferentes entre si. Os valores obtidos nas condições indução/argônio e indução/vácuo foram semelhantes entre si (p > 0,05) e menores que os obtidos nas condições indução/ar e maçarico, estes últimos semelhantes entre si (p > 0,05). A microdureza das ligas é dependente da composição da liga e do método de fundição. A dureza das ligas de Ni-Cr foi maior quando fundidas nas condições indução/ar e maçarico.